Biochemical properties of nematode O-acetylserine(thiol)lyase paralogs imply their distinct roles in hydrogen sulfide homeostasis - Vozdek, Roman; Hnízda, Aleš; Krijt, Jakub; Será, Leona; Kožich, Viktor (Biochimica et biophysica acta, 2013)
O-Acetylserine(thiol)lyases (OAS-TLs) play a pivotal role in a sulfur assimilation pathway incorporating sulfide into amino acids in microorganisms and plants, however, these enzymes have not been found in the animal kingdom. Interestingly, the genome of the roundworm Caenorhabditis elegans contains three expressed genes predicted to encode OAS-TL orthologs (cysl-1-cysl-3), and a related pseudogene (cysl-4); these genes play different roles in resistance to hypoxia, hydrogen sulfide and cyanide. To get an insight into the underlying molecular mechanisms we purified the three recombinant worm OAS-TL proteins, and we determined their enzymatic activities, substrate binding affinities, quaternary structures and the conformations of their active site shapes. We show that the nematode OAS-TL orthologs can bind O-acetylserine and catalyze the canonical reaction although this ligand may more likely serve as a competitive inhibitor to natural substrates instead of being a substrate for sulfur assimilation. In addition, we propose that S-sulfocysteine may be a novel endogenous substrate for these proteins. However, we observed that the three OAS-TL proteins are conformationally different and exhibit distinct substrate specificity. Based on the available evidences we propose the following model: CYSL-1 interacts with EGL-9 and activates HIF-1 that upregulates expression of genes detoxifying sulfide and cyanide, the CYSL-2 acts as a cyanoalanine synthase in the cyanide detoxification pathway and simultaneously produces hydrogen sulfide, while the role of CYSL-3 remains unclear although it exhibits sulfhydrylase activity in vitro. All these data indicate that C. elegans OAS-TL paralogs have distinct cellular functions and may play different roles in maintaining hydrogen sulfide homeostasis.
Keywords: zvířata; proteiny Caenorhabditis elegans; Homeostasis; cysteinsynthasa; Animals; Caenorhabditis elegans; katalytická doména; Serine; Substrate Specificity; buněčné jádro; Hydrogen Sulfide; serin; Catalytic Domain; Caenorhabditis elegans Proteins; sulfan; kyanidy; substrátová specifita; Cysteine Synthase; Cell Nucleus; homeostáza; Cyanides